Second-Order Conditioning in Humans - Lee, Jessica C. (Frontiers in Behavioral Neuroscience, 2021)
In contrast to the large body of work demonstrating second-order conditioning in non-human animals, the evidence for second-order conditioning in humans is scant. In this review, I examine the existing literature and suggest theoretical and procedural explanations for why second-order conditioning has been so elusive in humans. In particular, I discuss potential interactions with conditioned inhibition, whether second-order conditioning is rational, and propose critical parameters needed to obtain the effect. I conclude that second-order conditioning is a real but difficult phenomenon to obtain in humans, and suggest directions for future research.